Influence of the use of gravity sets in a pressure volumetric infusion pump with an impact on the accuracy of infusion solution flows - Fiedorová, Klára; Augustynek, Martin; Penhaker, Marek (Lékař a technika, 2020)
The subject of the work was the experimental verification of the negative influence of gravity sets in a pressure volumetric infusion pump with an impact on the accuracy of infusion solution dosing. The quality criterion for gravity sets was the accuracy of the flow versus the reference set by the volumetric infusion pump. The solution consisted of 14-hour measurements with two types of gravity sets, Intrafix® Primeline sets were used as universal sets and Standardline IS 103 gravity sets. The insulin pump flow rate was set at 300 ml/h and 50 ml/h, and the actual flow rate of the infusion solution was recorded every hour using a graduated cylinder. Used gravity sets were also processed by mechanical tests, unused sets were subjected to these tests and the obtained data were compared with each other. Experiments carried out showed that at the set flow rate of 300 ml/h, the flow error with the universal set was -3% and at a set flow rate of 50 ml/h the error was +2.3%. Flow accuracy using gravity sets was worse, a flow error of -7.2% was detected for a flow rate of 50 ml/h and a flow error of -7.7% was measured for 300 ml/h. The volumetric pump used declares a tolerated inaccuracy of ± 3% when used with standard infusion sets. Based on the data, it can be concluded that the replacement of set types has an influence on the dosage of infusion solutions.
Keywords: infuzní pumpy; lidé; Infusion Pumps; Patient Safety; bezpečnost pacientů; Humans